Drag reduction in sports - Westerweel, J. (19th Annual Congress of the European College of Sport Science (ECSS), Amsterdam, 2. - 5. July 2014, 2014)
Drag resistance of a moving body in a fluid, that is air or water, comprises of form drag and skin friction drag. In most water-based sports, also wave drag contributes to the total drag. Evidently, drag implies a loss of the available power an athlete can utilize to improve his or her performance. Shape drag and wave drag can be reduced by means of the optimization of the athlete`s posture or shape of sports equipment. Skin friction depends on the properties of the material that is in contact with the moving fluid. In this paper we review the physical aspects of skin friction drag, and we consider different approaches that achieve an effective reduction of the skin friction. The flow adjacent to a surface is determined by the geometric, mechanical and physical properties of that surface. The skin friction can be reduced by means of changing the surface properties, or the flow conditions at the surface. Well-known examples are the application of strips or trip-wires to change the flow condition and induce a favorable transition to a turbulent flow. Also polymer additives and small gas bubbles can achieve a reduction of the skin friction by modifying the turbulence. Other approaches use structured surfaces, such as riblets and superhydrophobic surfaces or coatings.